2016
DOI: 10.18240/ijo.2016.11.22
|View full text |Cite
|
Sign up to set email alerts
|

Trends in ophthalmology journals: a five-year bibliometric analysis (2009-2013)

Abstract: While the USA and European countries are major contributors of ophthalmic research, the productivity of some Asian countries is growing impressively. The contribution of China, Korea and India is forecasted to outweigh that of Europe by 2023. Research expenditure is highly correlated with research productivity and these trends reflect the differing economic priorities across the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
1
6
0
1
Order By: Relevance
“…Our data demonstrated a statistically significant correlation of top-100 citation with top-tier medical school and residency training, but prestigious undergraduate education did not show a statistically significant correlation. Other studies have found that countries with more funding for ophthalmology research have higher productivity [13]. This finding is consistent with our results, as the top-100 researchers displayed an elevated proportion of authors with a residence in the USA, which leads the world in ophthalmology research funding [7].…”
Section: Discussionsupporting
confidence: 92%
“…Our data demonstrated a statistically significant correlation of top-100 citation with top-tier medical school and residency training, but prestigious undergraduate education did not show a statistically significant correlation. Other studies have found that countries with more funding for ophthalmology research have higher productivity [13]. This finding is consistent with our results, as the top-100 researchers displayed an elevated proportion of authors with a residence in the USA, which leads the world in ophthalmology research funding [7].…”
Section: Discussionsupporting
confidence: 92%
“…It also enables researchers to determine the range of research topics and identify new topics, and assists them in planning their research direction and predicting research trends [8]. A number of bibliometric studies have investigated the publishing trends in ophthalmology concerning the research output of specific countries or areas [9,10], subspecialties [11][12][13] or the production of a selection of ophthalmology journals [14]. To the best of our knowledge, there are no bibliometric analyses that have explored research related to DED.…”
Section: Introductionmentioning
confidence: 99%
“…This highlights that the USA and the other European countries possess developed economies, robust data management practices, and strong academic systems [ 27 , 28 ] . The USA and Europe were major contributors to global research trends in the field of ophthalmology, despite the impressive increase in research output from Asian countries [ 29 ] .…”
Section: Discussionmentioning
confidence: 99%